Consumption practices, an analysis of the rational use and disposal of medicines and dietary supplements (Research, Society and Development, 2025)
The general objective of this study is to promote educational actions among the academic community and the local population regarding the risks of self-medication and the proper disposal of medicines, encouraging safe and sustainable practices for public health and environmental preservation. This study is a social, qualitative and quantitative research designed as an experience report. The campaign collected expired or near-expired tablets from drugstores, a hospital pharmacy and local residents. The data showed a significant accumulation of medications used to treat chronic diseases. The educational actions helped clarify the risks of self-medication and the environmental impacts of improper disposal in household waste. Part of the valid medications was donated to a local health institution that supports people in vulnerable situations. The initiative brought students, professionals and the community closer together, strengthening practices of care, social responsibility and environmental protection.